2023
DOI: 10.3390/molecules28083299
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Mathematical Interpretation of Zero-Valent Iron NPs Using Nigella sativa Seed Tincture for Indemnification of Carcinogenic Metals Present in Industrial Effluents

Abstract: Zero-valent iron nanoparticles (ZVI-NPs) are utilized for the indemnification of a wide range of environmental pollutants. Among the pollutants, heavy metal contamination is the major environmental concern due to their increasing prevalence and durability. In this study, heavy metal remediation capabilities are determined by the green synthesis of ZVI-NPs using aqueous seed extract of Nigella sativa which is a convenient, environmentally friendly, efficient, and cost-effective technique. The seed extract of Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…As a blank, distilled water was used for the analysis. The increase in absorbance 700 nm indicated that the plant extract has the highest reducing power …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a blank, distilled water was used for the analysis. The increase in absorbance 700 nm indicated that the plant extract has the highest reducing power …”
Section: Methodsmentioning
confidence: 99%
“…The increase in absorbance 700 nm indicated that the plant extract has the highest reducing power. 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their size is approximately 100 to 10,000 times smaller than that of biological molecules such as enzymes, receptors, and antibodies [ 1 ]. Owing to their ultra-small size, large surface area, and high surface activity, NPs exhibit fascinating size-/structure-dependent properties and superiorities (e.g., electrical, magnetic, optical, chemical, biological) compared to their corresponding bulk materials [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the three main ecosystems on Earth, freshwater aquifers are essential to global ecology and the economy [ 1 ]. Water reservoirs are crucial for nutrient cycling and environmental preservation, but they are progressively being impacted by heavy metals, which may threaten their stability [ [2] , [3] , [4] ]. Heavy metals are highly hazardous to terrestrial and aquatic ecosystems and, therefore, to humans, birds, and aquatic life due to their toxicity, accumulative nature, and non-biodegradability [ 5 ].…”
Section: Introductionmentioning
confidence: 99%